DESIGN OF INDUCTION COIL FOR OXYGEN FREE COPPER PRODUCTION - S. Kazem, Murtadha; M. Abdulbaqi, Isam (Journal of Engineering and Sustainable Development, 2021)
This paper deals with the design of an induction coil (IC) intended to be used for an oxygen free copper production. This coil differs in design because it should be placed in a vacuum or in a chamber filled with noble gas, such as Argon. The designed coil must be suitable for melting the copper in this environment. The coil design means, using the simulation of the melting process to determine the best, coil geometry, type of crucible, the required current, frequency, the consumed power, and time required for this process. These results will be used to determine the parameters of the induction furnace AC power source suitable for feeding such a melting process efficiently. The Finite Element Analysis (FEA) intended to simulate the heating process to determine the best coil dimensions, and choosing the crucible. It is found that the best crucible used for the melting of copper is the carbon crucible.